TINJAUAN HUKUM PENYEBAR BERITA HOAX DI MEDIA SOSIAL MENURUT UNDANG-UNDANG INFORMASI TRANSAKSI ELEKTRONIK (ITE) / UNDANG-UNDANG NOMOR 11 TAHUN 2008 DAN PENYELESAIAN HUKUM - Saharuddin Saharuddin (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTActivities in the cyber space are virtual activities that have a very real impact even though the evidence is electronic. Accordingly, the subject of the culprit must also be qualified as a person who has committed a real legal act. In e-commerce activities, among others, the existence of an electronic document whose position is synchronized with documents made on paper. In this regard, it is necessary to consider the security and legal certainty in the utilization of information technology, media, and communication in order to develop optimally. Therefore, there are three approaches to maintain security in cyber space, namely the legal aspect, technological aspects, Social, cultural, and ethical. To overcome the disruption of security in the implementation of electronic systems, the legal approach is absolute because without legal certainty, the issue of utilizing information technology becomes not optimal. In principle, the act of spreading the hoax news that has a tendency as a criminal act of defamation, more concretely tends to qualify as a criminal act of defamation (laster). That is because the false news that is conveyed does not contain the truth, what he has allegedly never done for the accused, by the Criminal Code is classified as "slander". Associated with the distribution of news hoax that can harm the collective interests, the target of his actions is definitely fixed on the interests of the audience.  This act in the law is often to be included  with  the consequences of his actions;  (1) Whether to cause trouble;  (2) Or will it cause a sense of hatred towards a group.Keywords  :  Hoax, false news, social media, cyber